Estimation of Contribution and Emission-to-PM2.5 Conversion Rate by Each Local Government for Policy Support - Moon, Nankyoung; Seo, Jihyun; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
Air quality has cumulative and complicated characteristics with emission, advection, diffusion and chemical reactions of air pollutants. For the implementation of a PM2.5 improvement plan for a local government, it is needed to understand PM2.5 contributions of the source from neighboring local governments as well as the target local government. To quantitatively estimate the PM2.5 contributions, conversion rates of the precursor emissions to PM2.5 concentrations for a local government can be applied. However, it is difficult for the policy maker to prepare the conversion rate between the emission and concentration when the complicated nonlinear behaviors of air pollutants are considered. In this study, the contribution of PM2.5 source categories (point, mobile and area) and pollutants (NOx, SOx, NH3, VOC and PM2.5) was analyzed using WRF and CMAQ/BFM for 17 local governments. From the results of these contribution concentration and emissions by local governments, the conversion rate of PM2.5 were estimated for each source category and each pollutant. The conversion rate that explains how much PM2.5 concentration is generated by one ton of the prcursor emissions can be used to examine the effects of air quality policies such as emission controls. In addition, it can be usefully used in the pre-evaluation step before the complicated three-dimensional air quality modeling by quantitatively analyzing the influence of PM2.5 due to the changed emission.
Keywords: CMAQ; Conversion rate; PM2.5; PM2.5 precursors; Policy support